GP255 'Mycoombe' mhealth app – a pilot study. (June 2019) - McGrath, Robert; Barrett, Tina; O'Cuiv, Liam; Caruth, Georsan; Walsh, Aisling; Biesma, Regien; Turner, Michael; Miletin, Jan; Doolan, Anne
Abstract : Background: Over the past decade, mobile health (mHealth) has become a burgeoning field within public health. mHealth applications (apps) are software that are incorporated into smartphones to improve health outcome and health care services. A number of mHealth apps are focused on maternal and child health. The quality of and evidence base for the information these provide can be unreliable and not in line local healthcare practices. Our aim was to perform a pilot study to determine the feasibility of using a unique mHealth app 'MyCoombe' in a cohort of new mothers and assess the acceptability of this app to study participants. Methods: We developed a unique mHealth application 'MyCoombe' for Android, the content of which was focused on newborn health and early development, newborn feeding and maternal postpartum health and drawn from reliable evidence based sources, which were in line with local healthcare practices. Ethical approval was obtained from the Coombe Women & Infants University Hospital (CWIUH) Research Ethics Committee. We then performed a prospective observational cohort study within CWIUH from April to November 2017. Mothers attending routine antenatal clinics were approached, provided with study information and written informed consent obtained. Patient demographics were recorded and a link to download 'MyCoombe' was provided to study participants. At six weeks postpartum, a feedback survey was sent to all active participants. Results: We recruited 116 mothers in the study period, each of whom were given a download link to 'MyCoombe'. Forty percent (46/116) downloaded the app and logged in at least once. The app was accessed 289 times in total, for an average of 6.28 interactions per participant. These 46 were sent a link to a feedback survey. Twenty-six percent (12/46) participants completed the survey. Fifty percent of respondents reported that the app was missing features they required. One respondent reported that it had too much information, while one respondent stated that the app should have more information and topics to be more acceptable to the user. Sixty-six percent of respondents stated that they would recommend 'MyCoombe' to friends and family. Conclusion: The information needs of new mothers are multi-faceted and vary significantly between individuals. While it was feasible to use 'MyCoombe' in a cohort of new mothers, there was significant participant attrition after recruitment with 60% (70/116) not downloading the app. Of survey responders 66% percent (8/12) found the app to be acceptable and would recommend to friends and family.